Nascent application of aerobic granular sludge for recirculating aquaculture system effluent treatment: Performance, granule formation, and microbial community - Suhonen, Talvikki; Al-Juboori, Raed A.; Kruglova, Antonina; Pulkkinen, Jani; Vielma, Jouni; Mikola, Anna (Elsevier BV, 2023)
This study presents for the first time an evaluation of the feasibility of aerobic granular sludge (AGS) for treating recirculating aquaculture system (RAS) effluent in a sequential batch reactor configuration for nutrient removal. An AGS process was started using synthetic wastewater to grow the granules, and the feed was then switched to RAS effluent, and a systematically decreasing carbon supplementation was applied. Total nitrogen removal significantly decreased from around 75 % to as low as 13 %, but granules could restore their performance when allowed enough time (2 weeks) to acclimate to the change in feed. The dynamics of AGS microbial communities were followed by Illumina sequencing. A high abundance of microbial populations—indicating dense and stable granules—was observed after 97 days of operation with RAS wastewater. In particular, the genera Neomegalonema, Hydrogenophaga, Thauera, Bdellovibrio, Flavobacterium, and Pseudomonas represented most of the community, showing the heterotrophic, denitrifying, and phosphorus-accumulating potential of the studied operational design. The AGS showed promising results for a small-footprint solution for RAS treatment, but the energy consumption of aeration and carbon addition still requires further development.
Keywords: kalanviljely; jäteveden käsittely; Recirculating aquaculture system; Aerobic granular sludge; Nitrogen removal; Microbial community